Antenatally detected functional adrenocortical adenoma: A case report and review of current literature - Vivek Kumar Singh; Chitrali Khanna; V Shankar Raman; Akhil Goel (Wolters Kluwer Medknow Publications, 2022)
Pediatric adrenocortical tumors (ACTs) are rare entities with an incidence of 0.2% of all pediatric tumors. Only two cases of antenatally detected ACT have been reported in the literature. Our case is the first report of an antenatally detected suprarenal mass which manifested with postnatal virilizing features and was proven to be adrenocortical adenoma on histology.